Voltammetric study of ds-DNA–flutamide interaction at carbon paste electrode - Pradeep K. Brahman; Riyaz A. Dar; Krishna S. Pitre (Arabian Journal of Chemistry, 2016)
Differential pulse voltammetry (DPV) has been used to develop an electro-analytical procedure for the determination of flutamide and evaluate its interaction with DNA immobilised on the carbon paste electrode (CPE) surface. In 0.3 M phosphate buffer (pH 7.0 ± 0.01) as supporting electrolyte flutamide produced a well defined DPV peak at Ep = −0.75 V vs. SCE. The DPV study on the DNA–flutamide interaction clearly demonstrated that flutamide interacts preferentially with adenine and guanine groups in DNA. Thus, enabling to assign mechanism of action of the anticancer drug, flutamide. The developed method was successfully applied to the determination of flutamide in pharmaceutical formulations. The work has been supplemented by UV spectral study.